2010
DOI: 10.1111/j.1462-5822.2010.01538.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of δ-toxin by Staphylococcus aureus mediates escape from phago-endosomes of human epithelial and endothelial cells in the presence of β-toxin

Abstract: SummaryStaphylococcus aureus is able to invade nonprofessional phagocytes by interaction of staphylococcal adhesins with extracellular proteins of mammalian cells and eventually resides in acidified phago-endosomes. Some staphylococcal strains have been shown to subsequently escape from this compartment. A functional agr quorumsensing system is needed for phagosomal escape. However, the nature of this agr dependency as well as the toxins involved in disruption of the phagosomal membrane are unknown. Using a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
120
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(124 citation statements)
references
References 59 publications
(111 reference statements)
3
120
1
Order By: Relevance
“…This observation is consistent with a report by Kobayashi et al describing the escape of different USA300 strains from PMNs, where the investigators concluded that escape from PMNs by S. aureus was independent of toxins when evaluated 6 h postinfection (42). In light of this new role for LukAB, which may be shared with other staphylococcal factors such as delta hemolysin and beta hemolysin (48) and PSMs (38,43), vaccine strategies that aim to promote phagocyte-mediated killing of S. aureus through opsonization may prove to be ineffective. Our data show that opsonization does cause PMN-mediated killing of USA300, but factors such as LukAB allow the early escape and propagation of surviving bacteria.…”
Section: Discussionsupporting
confidence: 82%
“…This observation is consistent with a report by Kobayashi et al describing the escape of different USA300 strains from PMNs, where the investigators concluded that escape from PMNs by S. aureus was independent of toxins when evaluated 6 h postinfection (42). In light of this new role for LukAB, which may be shared with other staphylococcal factors such as delta hemolysin and beta hemolysin (48) and PSMs (38,43), vaccine strategies that aim to promote phagocyte-mediated killing of S. aureus through opsonization may prove to be ineffective. Our data show that opsonization does cause PMN-mediated killing of USA300, but factors such as LukAB allow the early escape and propagation of surviving bacteria.…”
Section: Discussionsupporting
confidence: 82%
“…Here, we show that within 1 h of macrophage infection, the majority of USA300 bacteria are sequestered within acidic phagosomes and that the bacteria remain in acidic compartments during 8 h of infection. Previous studies demonstrated escape of S. aureus strains from vacuoles of nonphagocytic cells within hours of infection (13,55,61,62). However, we demonstrate that during macrophage infection, over 90% of USA300 bacteria are enclosed within intracellular compartments as that proportion of bacteria was localized within acidic vesicles at 8 h p.i.…”
Section: Discussioncontrasting
confidence: 37%
“…Recent work showed that staphylococci can escape from their initial phagosomes to the cytoplasm by expressing delta-toxin and/or the PSM-alpha protein, whereas some strainspecific differences are possible (184,185). The location where bacteria form SCVs and persist for long periods might be the cytoplasm, but this is not precisely known.…”
Section: Other Factors That Induce the Formation Of Scvs During In VImentioning
confidence: 99%